1998
DOI: 10.1046/j.1471-4159.1998.70052045.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cellular Compartments Involved in Processing of Cathepsin E in Primary Cultures of Rat Microglia

Abstract: Cathepsin E is a major nonlysosomal, intracellular aspartic proteinase that localizes in various cellular compartments such as the plasma membrane, endosome‐like organelles, and the endoplasmic reticulum (ER). To learn the segregation mechanisms of cathepsin E into its appropriate cellular destinations, the present studies were initiated to define the biosynthesis, processing, and intracellular localization as well as the site of proteolytic maturation of the enzyme in primary cultures of rat brain microglia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 51 publications
3
70
0
Order By: Relevance
“…Cathepsin E is an intracellular aspartic protease homologous to cathepsin D [22,35]. Cathepsin D is localized within the lysosomes of most cells [9] while cathepsin E is localized in various non-lysosomal compartments such as the endosome, the endoplasmic reticulum and the Golgi complex and has a limited cell and tissue distribution [26,35,37,41]. Cathepsin E has been detected in mouse, rabbit and rat macrophages [2,9,30,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin E is an intracellular aspartic protease homologous to cathepsin D [22,35]. Cathepsin D is localized within the lysosomes of most cells [9] while cathepsin E is localized in various non-lysosomal compartments such as the endosome, the endoplasmic reticulum and the Golgi complex and has a limited cell and tissue distribution [26,35,37,41]. Cathepsin E has been detected in mouse, rabbit and rat macrophages [2,9,30,36].…”
Section: Discussionmentioning
confidence: 99%
“…It is very well possible that this pH dependency arises from the low pH-autocatalytic conversion of procathepsin E to the mature active form [37], which cleaves one of the PRRSV structural proteins. Cathepsin E has a cleavage specificity and maximal activity at around pH 6.0 [3,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether cathepsin E is essential for MHC class II Ag presentation. Because cathepsin E exists in APC endosomes as the mature enzyme (23,27), and because cathepsin E expression is increased upon stimulation with IFN-␥ and LPS, known to induce MHC class II expression and costimulatory molecules (55), it is relevant to determine to what extent cathepsin E activity influences MHC class II-restricted Ag presentation. The present results showed for the first time that cathepsin E deficiency strongly affected the presentation of OVA by macrophages and DCs to its specific T cell hybridomas, implying that cathepsin E is involved in antigenic presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in vitro studies using purified proteases and their inhibitors have demonstrated that cathepsin D (18 -21) and/or cathepsin E (21-24) might play a role in antigenic peptide generation. Further studies using APC derived from cathepsin D-deficient mice have shown that cathepsin D is not essential for MHC class II Ag presentation (23,(25)(26)(27). However, to date it remains speculative whether cathepsin E is directly involved in the MHC class II Ag presentation in APC.…”
mentioning
confidence: 99%
“…In a human organism, cathepsin E occurs in: erythrocytes, thymus, dendritic cells, epithelial M cells, microglia cells, Langerhans cells, lymphocytes, epithelium of gastrointestinal tract, urinary bladder, lungs, osteoclasts, spleen and lymphatic nodes [9][10][11][12][13][14]. However, it does not occur in human neutrophiles or bovine erythrocytes [15] (Table 2).…”
Section: Distributionmentioning
confidence: 99%